Fantastic Mr. Dahl - Rosen, Michael, 1946-; Blake, Quentin (New York : Puffin, 2012)
Presents the story of the author known for such classic works of children's literature as "Charlie and the Chocolate Factory" and "Matilda," sharing details from Dahl's personal life while revealing the inspirations for his stories.
Keywords: Dahl, Roald -- Juvenile literature; Dahl, Roald; Dahl, Roald; Authors, English -- 20th century -- Biography -- Juvenile literature; Children's stories -- Authorship -- Juvenile literature; Authors; Children's stories -- Authorship; English authors -- Biography; Children's stories -- Authorship